Before and again - Delinsky, Barbara (St. Martin's Press, 2018)
Mackenzie Cooper took her eyes off the road for just a moment but the resulting collision was enough to rob her not only of her beloved daughter but ultimately of her marriage, family, and friends<U+2015>and thanks to the nonstop media coverage, even her privacy. Now she lives in Vermont under the name Maggie Reid, in a small house with her cats and dog. She<U+2019>s thankful for the new friends she<U+2019>s made<U+2015>though she can<U+2019>t risk telling them too much. And she takes satisfaction in working as a makeup artist at the luxurious local spa, helping clients hide the visible outward signs of their weariness, illnesses, and injuries. Covering up scars is a skill she has mastered. Her only goal is to stay under the radar and make it through her remaining probation. But she isn<U+2019>t the only one in this peaceful town with secrets. When a friend<U+2019>s teenage son is thrust into the national spotlight, accused of hacking a powerful man<U+2019>s Twitter account, Maggie is torn between pulling away and protecting herself<U+2015>or stepping into the glare to be at their side. As the stunning truth behind their case is slowly revealed, Maggie<U+2019>s own carefully constructed story begins to unravel as well. She knows all too well that what we need from each other in this difficult world is comfort. But to provide it, sometimes we need to travel far outside our comfort zones.